Rigid Reachability - Ganzinger, Harald; Jacquemard, Florent; Veanes, Margus (Proceedings of the 4th Asian Computing Science Conference on Advances in Computing Science (ASIAN 98), 1998)
We show that rigid reachability, the non-symmetric form of rigid E-unification, is undecidable already in the case of a single constraint. From this we infer the undecidability of a new rather restricted kind of second-order unification. We also show that certain decidable subclasses of the problem which are P-complete in the equational case become EXPTIME-complete when symmetry is absent. By applying automata-theoretic methods, simultaneous monadic rigid reachability with ground rules is shown to be in EXPTIME.